Short repeated elements in the upstream regulatory region of the SUC2 gene of Saccharomyces cerevisiae. - Sarokin, L (1986)
Expression of secreted invertase from the SUC2 gene is regulated by carbon catabolite repression. Previously, an upstream regulatory region that is required for derepression of secreted invertase was identified and shown to confer glucose-repressible expression to the heterologous promoter of a LEU2-lacZ fusion. In this paper we show that tandem copies of a 32-base pair (bp) sequence from the upstream regulatory region activate expression of the same LEU2-lacZ fusion. The level of expression increased with the number of copies of the element, but was independent of their orientation; the expression from constructions containing four copies of the sequence was only twofold lower than that when the entire SUC2 upstream regulatory region was present. This activation was not significantly glucose repressible. The 32-bp sequence includes a 7-bp motif with the consensus sequence (A/C)(A/G)GAAAT that is repeated at five sites within the upstream regulatory region. Genetic evidence supporting the functional significance of this repeated motif was obtained by pseudoreversion of a SUC2 deletion mutant lacking part of the upstream region, including two copies of the 7-bp element. In three of five pseudorevertants, the mutations that restored high-level SUC2 expression altered one of the remaining copies of the 7-bp element.